Ensaios sobre política fiscal na América Latina - Guerra, Daniel Lins Batista (2022)
The present study has as its general objective to explore the determining elements for fiscal policies in Latin America, whose analysis is developed in three axes. First, the relations between debt levels and product growth in economies in the Latin American region are investigated, based on the discussion opened by Reinhart and Rogoff (2010). The results show that the evolution and level of public debt are statistically significant with the performance of growth both in the short and long term for Latin American countries. Next, the relations between fiscal performance and political-institutional factors were analyzed, following the debate formed in Rogoff (1987) and Roubini and Sachs (1988). It was evidenced that part of the macroeconomic and fiscal results go through political-economic cycles and are affected by the political-institutional structure provided by the countries. Finally, tax multipliers were calculated for different expenditure components, for periods of high and low indebtedness, resuming the discussion elaborated in Huidrom et al. (2016). The pattern of indebtedness in the period surveyed did not show to be a restrictive factor in the power of tax multipliers. The components of capital expenditures have greater immediate effects on growth, compared to those focused on current spending. At the time when, surprisingly, a positive effect was found in the boost in tax collection.